EFEKTIVITAS PENGENDALIAN INTERNAL DALAM PENGELOLAAN KLAIM ASURANSI KREDIT DAN DAMPAKNYA TERHADAP MITIGASI RISIKO KEWAJIBAN SEGERA (KWS) PADA PT BPR BKK JATENG (PERSERODA) KC MAGELANG - Salamah, Umi; Prihastiwi, Diah Agustina (Journal Accounting International Mount Hope, 2025)
PT BPR BKK Jateng (Perseroda) is one of the Regional-Owned Enterprises (BUMD) in Central Java Province engaged in financial services, especially as a People's Credit Bank (BPR). This company has various branch offices spread across various regions of Central Java, including in Magelang City. As a financial institution, BPR has a strategic role in distributing financing to the community, but is also faced with challenges in managing internal control risks. This study aims to analyze the effectiveness of internal control in managing credit insurance claims at PT BPR BKK Jateng (Perseroda) KC Magelang and its impact on mitigating the risk of immediate liabilities (KWS). Effective internal control is an important element in ensuring the smooth running of the credit insurance claim management process, reducing potential risks, and improving corporate governance. The research method used is a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the implementation of good internal control can minimize the risk of immediate liabilities, increase operational efficiency, and strengthen corporate risk management. This research is expected to contribute to PT BPR BKK Jateng (Perseroda) KC Magelang in optimizing the internal control system to support the sustainability of the company's operations.